Fiordland: the ecological basis for ecosystem management - SR Wing; L Jack (New Zealand Journal of Marine and Freshwater Research, 2014)
Marine ecosystems are structured by physical and biological influences on: production and transport of organic matter; population dynamics; and food web architecture. Here, we review how scientific insights in the Fiordland marine area have supported ecosystem management. Fiordland is a case study for four ecological paradigms: 1. physical forcing of productivity; 2. subsidies of organic matter; 3. reproductive source‐sink dynamics; and 4. stability of food web architecture. Understanding of these processes underpinned development of a network of marine reserves comprising the first regional experiment in marine ecosystem management for New Zealand. Monitoring the marine reserves demonstrated increasing abundance of rock lobsters ( Jasus edwardsii ) and blue cod ( Parapercis colias ). Further, analyses of reef fish communities indicated reserves supported abundant high trophic level omnivores, leading to stable communities and intact food webs. These results demonstrated success in two of the objectives of ecosystem management–enhanced production of exploited species and preservation of biodiversity.